Republic of Madagascar : Request for an Arrangement Under the Extended Credit Facility: First Review Under the Staff Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the Republic of Madagascar's request for an arrangement under the Extended Credit Facility (ECF) and first review under the Staff Monitored Program (SMP). Madagascar's macroeconomic performance was broadly satisfactory under the SMP, which ran from September 2015 to the end of March 2016. The authorities' ECF-supported program, anchored on their National Development Plan, aims to reinforce macroeconomic stability and promote sustainable and inclusive growth. It focuses on promoting robust and inclusive growth, combining improved access to education, health care, and social protection with infrastructure and private sector development. The IMF staff supports the authorities' request for an ECF.